Game Developer Competition Between USA and China - Ferric Limano; Pratikta Aditya Setiawan (Journal of Games, Game Art, and Gamification, 2019)
This study aims to obtain a comparison between two biggest economic Country, and see they focus on games industry global market. In this study researchers took the data from secondary data in global market game then analyzed data quantitatively and objectively by comparing data with USA & China video game market as the subject. The result of this study expected to be used as recommendation for game developers in choosing which platform to focus in designing their games by following patterns of subject reference that has been existed, in accordance with a model in design business criteria.